Smoking, DNA Adducts and Number of Risk DNA Repair Alleles in Lung Cancer Cases, in Subjects with Benign Lung Diseases and in Controls - Marco Peluso; Armelle Munnia; Sara Piro; Alessandra Armillis; Marcello Ceppi; Giuseppe Matullo; Riccardo Puntoni (Journal of Nucleic Acids)
Smoke constituents can induce DNA adducts that cause mutations and lead to lung cancer. We have analyzed DNA adducts and polymorphisms in two DNA repair genes, for example, XRCC1 Arg194Trp and Arg399Gln genes and XRCC3 Thr241Met gene, in 34 lung cancer cases in respect to 30 subjects with benign lung cancer disease and 40 healthy controls. When the study population was categorized in base to the number of risk alleles, adducts were significantly increased in individuals bearing 3-4 risk alleles (OR=4.1 95% C.I. 1.28–13.09, P=.009). A significant association with smoking was noticed in smokers for more than 40 years carrying 3-4 risk alleles (OR=36.38, 95% C.I. 1.17–1132.84, P=.040). A not statistically significant increment of lung cancer risk was observed in the same group (OR=4.54, 95% C.I. 0.33–62.93, P=.259). Our results suggest that the analysis of the number of risk alleles predicts the interindividual variation in DNA adducts of smokers and lung cancer cases.